How Successful Are Banking Sector Reforms in Emerging Market Economies? Evidence from Impact of Monetary Policy on Levels and Structures of Firm Debt in India - Sumon K. Bhaumik; Ali M. Kutan; Sudipa Majumdar (Institute for the Study of Labor (IZA), 2016)
Many emerging markets have undertaken significant financial sector reforms especially in their banking sectors that have been quite critical for both financial development and real economic activity. In this paper, we investigate the success of banking reforms in India where significant banking reforms have been introduced since 1990s. Using the argument that well-functioning credit markets would reflect a bank channel for monetary policy at work, we test whether a change in monetary policy has predictable impact on borrowing behaviour of several types of firms, including business group affiliated, unaffiliated private firms, state-owned firms and foreign firms. The empirical results suggest that unaffiliated private firms have the most vulnerable to monetary policy stance during tight policy regimes. We also find that during tight monetary policy regimes, smaller firms are much more affected by monetary policy than large firms. In an easy money regime, monetary policy and the associated change in interest rate does not affect change in bank credit, change in total debt and the proportion of bank credit in total debt for any of the firms. We discuss the policy implications of the findings.
Keywords: E52; G21; G28; G32; O16; 330; banking reforms; monetary policy; credit markets; bank debt; debt structure